Status Kerentanan Nyamuk Anopheles sundaicus Terhadap Insektisida Cypermerthrin Di Kabupaten Garut - Nunung Seniawati; Lukman Hakim (Loka Litbang Kesehatan Pangandaran, 2010)
At the time of high vector populations and malaria transmission is in progress, it is necessary to use insecticides to control vector using the house spraying. To get the results as objective the eradication of the vector that is able to suppress the vector population sothat no longer play a role in malaria transmission, the insecticide used should be effective against mosquitoes and the mosquitoes are still susceptible to the insecticide used. To determine the level of malaria vector mosquito susceptibility to insecticides, in the territory of Garut district has conducted susceptibility tests of Anopheles sundaicus mosquitoes to insecticides Cypermethrin held in November up to December 2008. Mosquitoes testedwere captured in the form of larvae from ponds and estuaries in Karyamukti Cibalong Garut, and then reared in the field insektarium. The adult level were then tested for their susceptibility.Mosquito susceptibility tests conducted using the WHO Susceptibility Test Kit as many as four repetitions performed simultaneously, while the insecticide used in the form of impragnated paper with a dose of 0.05%From tests it is known that mosquito mortality rate up to 100% test. This indicates that the mosquito An. sundaicus in Garut regency of West Java, is still susceptible to the insecticide Cypermenthrin. Therefore, it can still be used in the eradication of malaria vectors in the recommended dosage of 0.20 g/m2.